Elephantopus scaber Linn Extract Inducing Apoptosis and Activate Caspase Cascade in T47D Cancer Cell Line: Elephantopus scaber Linn Extract Inducing Apoptosis and Activate Caspase Cascade in T47D Cancer Cell Line - Nurkhasanah, Mahfudh; Sulistyani, Nanik; Anugrah Putri, Raga Revamia (Iranian Journal of Pharmaceutical Sciences, 2019)
Elephantopus scaber Linn. was used traditionally for treating various diseases. Previous studies found the cytotoxicity of this herb against differentcell lines. This study aimed to determine the effectiveness of the ethanolic extract of E.scaberin inducing apoptosis by observing itseffect on caspase cascade.This ethanolic extract was obtained by maceration method using 96% ethanol. It was fractionated with petroleum ether to discard compounds with very low polarity.This step wasfollowed bythe fractionation with chloroform to isolate compounds with optimum polarity. The soluble part in chloroform was dried and used for the assay. The immunocytochemistry method used specific antibodies for caspase-8, caspase-3, and caspase-9 to observe the expressions of each caspase. T47D cell line was treated with the chloroform fraction of E. scaber with the concentrations of 7.06 μg/ml and 3.53μg/ml. The results of the immunocytochemistry showed that this chloroform fraction increased the expressions of caspase-8, caspase-3, and caspase-9 proteinssignificantly.Such increase led to apoptotic cells.This finding supported the development of E.scaber extract as ananticancer agent.